A pharmacist-led medication review service with a deprescribing focus guided by implementation science - Alaa Eddine, Nada; Schreiber, James; El-Yazbi, Ahmed F.; Shmaytilli, Haya; Amin, Mohamed Ezzat Khamis (Frontiers in Pharmacology, 2023)
Background: Little research addressed deprescribing-focused medication optimization interventions while utilizing implementation science. This study aimed to develop a pharmacist-led medication review service with a deprescribing focus in a care facility serving patients of low income receiving medications for free in Lebanon followed by an assessment of the recommendations’ acceptance by prescribing physicians. As a secondary aim, the study evaluates the impact of this intervention on satisfaction compared to satisfaction associated with receiving routine care. Methods: The Consolidated Framework for Implementation Research (CFIR) was used to address implementation barriers and facilitators by mapping its constructs to the intervention implementation determinants at the study site. After filling medications and receiving routine pharmacy service at the facility, patients 65 years or older and taking 5 or more medications, were assigned into two groups. Both groups of patients received the intervention. Patient satisfaction was assessed right after receiving the intervention (intervention group) or just before the intervention (control group). The intervention consisted of an assessment of patient medication profiles before addressing recommendations with attending physicians at the facility. Patient satisfaction with the service was assessed using a validated translated version of the Medication Management Patient Satisfaction Survey (MMPSS). Descriptive statistics provided data on drug-related problems, the nature and the number of recommendations as well as physicians’ responses to recommendations. Independent sample t-tests were used to assess the intervention's impact on patient satisfaction. Results: Of 157 patients meeting the inclusion criteria, 143 patients were enrolled: 72 in the control group and 71 in the experimental group. Of 143 patients, 83% presented drug-related problems (DRPs). Further, 66% of the screened DRPs met the STOPP/START criteria (77%, and 23% respectively). The intervention pharmacist provided 221 recommendations to physicians, of which 52% were to discontinue one or more medications. Patients in the intervention group showed significantly higher satisfaction compared to the ones in the control group (p<0.001, effect size=1.75). Of those recommendations, 30% were accepted by the physicians. Conclusion: Patients showed significantly higher satisfaction with the intervention they received compared to routine care. Future work should assess how specific CFIR constructs contribute to the outcomes of deprescribing-focused interventions.